Vascular Adaptations to Spaceflight: Results from the Vascular Series Experiments - Hughson, Richard; Greaves, Danielle K; Arbeille, Philippe (Revista Cubana de Investigaciones Biomédicas, 2019)
Long-duration spaceflight on the International Space Station (ISS) could be detrimental to astronaut health because of the prolonged period of physical unloading and other stressful factors including isolation and radiation in the microgravity environment. The Vascular Series of experiments was designed to investigate the effects of spaceflight on the arteries. We tested the hypothesis that removal of the normal head-to-foot gravitational force experienced everyday on Earth would cause increased stiffness of the carotid arteries as well as development of insulin resistance that could also impact vascular health. In Vascular, the first experiment of the series, results confirmed increased carotid artery stiffness and insulin resistance; but, the study also revealed a more generalized artery stiffness extending into the lower body. Hormonal and oxidative stress markers could have also influenced vascular health. The next experiments in the Vascular Series, Vascular Echo and Vascular Aging will advance investigations of vascular health employing the ECHO device that has remote robotic control of the ultrasound by experts on the ground to enhance image acquisition while on ISS, and to follow post-flight recovery processes. Vascular Aging will introduce oral glucose tolerance testing on ISS to further quantify the magnitude and the cause of insulin resistance and impaired glucose handling during spaceflight. Together, these studies will provide critical information about the extent of vascular changes during spaceflight and will determine whether all factors that contribute to increased arterial stiffness are reversible, or if there are long-term cardiovascular health consequences.